FATWA HARAM INFLUENCE CONSUMER ATTITUDES TOWARD CIGARETTE (CASE STUDY ON STUDENTS ISLAMIC STATE UNIVERSITY FACULTY OF ISLAMIC Sunan Kalijaga YOGYAKATA) - Ma’ruf, Sugeng (Management, 2010)
" Fatwas have a high status in Islam. Fatwa considered to be one alternative that could break the ice in the development of Islamic law. Islamic law is the stipulation can not be separated from religious arguments (as-an-nushush syariiyah). Fatwas as ijtihad involves only the arguments that are dzanniy (not sure). The laws are already qathiy (certainly) not be extracted by the process of ijtihad. On Tuesday dated 09 March 2010 in Jakarta, Muhammadiyah's central leadership through the Legal Affairs Committee issued a fatwa haram smoking. Expenditure fatwa haram to smoke is because of Muhammadiyah feel the negative effects of cigarettes in the field of health, social, and economic. According to data from the World Health Organization (WHO), Indonesia is the third largest number of smokers. Other studies mentioned, 6 of 10 people were smokers, and 8 out of 10 people exposed to cigarette smoke. Student Affairs Faculty of Sharia Islamic University Sunan Kalijaga Yogyakarta was chosen as respondents because other than as consumers, students, faculty better understand and further explore the science of the Personality (law) which must have its own views about the fatwa haram according to the criteria of sample diambil. From the analysis of MAM (multiatribute Attitude Model) Fishbein, the influence of illicit cigarettes fatwa is neutral views of the characteristics of age, based on attributes of the legal establishment of a fatwa (37.8), attributes the effectiveness of a fatwa (33.9), attributes of health considerations (45), attribute considerations social (40.6) and the attributes of economic considerations (39.7). Differences consumer attitudes towards illicit cigarette fatwa based on the characteristics of age, seen from the legal basis for the determination of attributes X counting 2.146 fatwa, fatwa effectiveness attributes X counting 2.322, attributes X counting 1.544 health considerations, social considerations attributes X counting 1.920, attributes X counting economic considerations 0.717, and 5.591 X table then there is no difference in consumer attitudes based on age characteristics of the fatwa haram rokok." Keyword: MAM, fatwa, the MUI, Cigarettes